Investigation of the active thickness of solid oxide fuel cell electrodes using a 3D microstructure model - Cai,Q; Adjiman,CS; Brandon,NP (Electrochimica Acta, 2011)
A 3D microstructure model is used to investigate the effect of the thickness of the solid oxide fuel cell (SOFC) electrode on its performance. The 3D microstructure model, which is based on 3D Monte Carlo packing of spherical particles of different types, can be used to handle different particle sizes and generate a heterogeneous network of the composite materials from which a range of microstructural properties can be calculated, including phase volume fraction, percolation and three phase boundary (TPB) length. The electrode model can also be used to perform transport and electrochemical modelling such that the performance of the synthetic electrode can be predicted. The dependence of the active electrode thickness, i.e. the region of the anode, which is electrochemically active, on operating over-potential, electrode composition and particle size is observed. Operating the electrode at an over-potential of above 200 mV results in a decrease in the active thickness with increasing over-potential. Reducing the particle size dramatically enhances the percolating TPB density and thus the performance of the electrode at smaller thicknesses; a smaller active thickness is found with electrodes made of smaller particles. Distributions of local current generation throughout the electrode reveal the heterogeneity of the 3D microstructure at the electrode/electrolyte interface and the dominant current generation in the vicinity of this interface. The active electrode thickness predicted using the model ranges from 5 μm to 15 μm, which corresponds well to many experimental observations, supporting the use of our 3D microstructure model for the investigation of SOFC electrode related phenomena.